The Devil is in the Details: Identifying the Unbiased Link between Access to Alcohol and Criminal Behavior - Kabir Dasgupta; Christopher Erwin; Alexander Plum (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2020)
The minimum alcohol purchasing age in New Zealand was lowered from 20 to 18 in December 1999. Focusing on two distinct legislative regimes, we utilize a national-level census of criminal convictions to examine the impact of unrestricted alcohol purchasing rights on alcohol-related crime. Our study reveals that overall trends in alcohol-related crimes are obscured by offences that can only be prosecuted up to a certain age. After removing confounding influences from additional regulations that hold relevance under one legislative regime but not the other, we do not find a statistically meaningful increase in overall measures of alcohol-related crimes at the minimum legal alcohol purchasing age. Our analysis suggests that compared to more commonly analyzed minimum legal drinking age legislation, governmental regulations that allow limited exposure to moderated drinking experiences prior to permitting alcohol purchasing rights might be more effective in mitigating alcohol-induced risky behaviors.
Keywords: C21; I12; I18; K14; K42; 330; minimum legal purchasing age; alcohol-related crime; court charges; youth behavior; regression discontinuity